Students' Understanding of Heredity and Variation - Behera, Prajna Paramita (SCHOOL SCIENCE, 2014)
The present study examines the pedagogical knowledge of students on heredity and variation. Questionnaires were administered in secondary/senior secondary/undergraduate level students. The comparison of understanding of students of different levels and various classes has been examined .The analysis indicates that the students’ understanding of Mendelian inheritance carry a great variation. Interestingly, 2nd year undergraduate students performed better than 4th year undergraduate students. The reason may be attributed to the fact that student-teachers have developed more interest in the curriculum so they perform well in their professional life .The students of school level need better in-depth understanding to develop more interest in the advanced technology of gene and genetics